Impact of non-migrating tides on the low latitude ionosphere during a sudden stratospheric warming event in January 2010. (June 2018) - McDonald, S.E.; Sassi, F.; Tate, J.; McCormack, J.; Kuhl, D.D.; Drob, D.P.; Metzler, C.; Mannucci, A.J.
Abstract: The lower atmosphere contributes significantly to the day-to-day variability of the ionosphere, especially during solar minimum conditions. Ionosphere/atmosphere model simulations that incorporate meteorology from data assimilation analysis products can be critically important for elucidating the physical processes that have substantial impact on ionospheric weather. In this study, the NCAR Whole Atmosphere Community Climate Model, extended version with specified dynamics (SD-WACCM-X) is coupled with an ionospheric model (Sami3 is Another Model of the Ionosphere) to study day-to-day variability in the ionosphere during January 2010. Lower atmospheric weather patterns are introduced into the SAMI3/SD-WACCM-X simulations using the 6-h Navy Operational Global Atmospheric Prediction System-Advanced Level Physics High Altitude (NOGAPS-ALPHA) data assimilation products. The same time period is simulated using the new atmospheric forecast model, the High Altitude Navy Global Environmental Model (HA-NAVGEM), a hybrid 4D-Var prototype data assimilation with the ability to produce meteorological fields at a 3-h cadence. Our study shows that forcing SD-WACCM-X with HA-NAVGEM better resolves the semidiurnal tides and introduces more day-to-day variability into the ionosphere than forcing with NOGAPS-ALPHA. The SAMI3/SD-WACCM-X/HA-NAVGEM simulation also more accurately captures the longitudinal variability associated with non-migrating tides in the equatorial ionization anomaly (EIA) region as compared to total electron content (TEC) maps derived from GPS data. Both the TEC maps and the SAMI3/SD-WACCM-X/HA-NAVGEM simulation show an enhancement in TEC over South America during 17–21 January 2010, which coincides with the commencement of a stratospheric warming event on 19 January 2010. Analysis of the SAMI3/SD-WACCM-X/HA-NAVGEM simulations indicates non-migrating tides (including DW4, DE2 and SW5) played a role during 17–21 January in shifting the phase of the wave-3 pattern in the ionosphere on these days. Constructive interference of wave-3 and wave-4 patterns in the E × B drifts contributed to the enhanced TEC in the South American longitude sector. The results of the study highlight the importance of high fidelity meteorology in understanding the day-to-day variability of the ionosphere. Highlights: Modeled ionospheric variations during January 2010 due to the lower atmosphere. Model captures increase in TEC over South America during several days in January. High fidelity meteorology is important in understanding ionospheric variability.